Hermenêutica e medicina clínica: o encontro dialógico ou “o paciente como texto”? - Tomazi, Talia Giacomini (2025)
Recent developments in the philosophy of medicine present important non-reductionist approaches as alternatives to the naturalistic definition of health and disease (Carel, 2016; Svenaeus, 2000). Among these, the phenomenological-hermeneutic approach explores the experience of health and illness in terms of homelikeness and unhomelikeness, respectively (Svenaeus, 2000). It is argued that such a conceptualization impacts the goals of medicine, both in its practical and theoretical aspects. This paper focuses precisely on the topic of medical practice. The doctor-patient relationship is conceived as an essentially interpretative interaction between individuals in asymmetrical conditions, that is, occupying different perspectives. Thus, the following question arises: how can we characterize the hermeneutic aspect that constitutes the clinical encounter between doctor and patient? To provide an answer, Svenaeus’s (2000) phenomenological-hermeneutic approach articulates an interpretation of the relationship between clinician and patient based on shared understanding. Svenaeus grounds his approach on Heidegger’s notion of understanding, which is interpreted in non-intellectual terms, as a “being able to”. In the clinical encounter, it is crucial for the doctor to be able to understand the patient’s perspective and vice versa. Understanding, in turn, is fundamentally enabled through the shared language of a dialogue, gradually oriented toward the fusion of horizons (Gadamer, 2014) between doctor and patient. The questions and answers exchanged in the clinical encounter aim at a shared project of restoring homelikeness, that is, health for the patient. Svenaeus’s proposal also presents itself as an alternative to other hermeneutic approaches to medical practice that, for instance, emphasize the textual component of the clinical encounter. This perspective, known through the metaphor of “the patient as a text”, conceives the doctor-patient relationship as analogous to the reading and interpretation of a text (Daniel, 1986; Leder, 1990). In this study, we will reconstruct the arguments of both hermeneutic approaches and, finally, present the reasons why the interpretative dialogue more adequately characterizes the hermeneutic aspect of the clinical encounter, given that the doctor-patient relationship is spoken rather than written, as presupposed by the patient as a text approach.